PERANCANGAN SISTEM EXIT PERMIT BERBASIS WEB PADA DORMITORY MUKAKUNING - Halimah Tussa'Adiyah, Halimah; Sitohang, Sunarsan (Computer Science and Industrial Engineering, 2024)
As the COVID-19 pandemic spreads to 216 countries, outdoor activities such as sports, shopping, traveling, and even working at home are reduced to reduce the spread of the virus. This also affected employees living in the Batam dormitory. They have to ask the supervisor for permission to leave if they want to do things outside the dormitory area. However, the licensing system in the Mukakuning dormitory is still done manually, with a permission letter requested from the supervisor's office for permission to leave. This causes many licensing problems, one of which is the difficulty of getting an exit permit. which serves for a more organized and safer licensing process. The design of this system is carried out using the waterfall method, which is used in this study because this method is easier to use and easier to understand. The results showed that the web-based exit permit system can be used in the Mukakuning dormitory and can help more secure exit permit data collection. This system uses programming algorithms, QR cards, and black box system testing methods. The result is a system that is very well designed and can be used directly for the licensing process at the Mukakuning dormitory..